Enhanced Hydrogen Storage in Mg thin Flakes with dispersed Ni Nanoparticles prepared by High Energy Ball Milling (2024)
ABSTRACT: Hydrogen with its high e nergetic density ( 119 .7 MJ/ and facile production through water electrolysis , is a viable alternative energy source. Nevertheless, its low volumetric density and high flammability present challenges for mobile applications [ In response, s olid state storage of hydrogen using metal hydrides has emerged as a promising solution for secure transport and storage of this energy carrier , facilitating its u tilization as a clean fuel source [2], [ 3]. Magnesium, with its low density, natural abundance, affordability, and reversible hydrogenation /dehydrogenation capabilities, stands out as one of the most promising metals for this purpose [ 4]. However, optimizing its t hermodynamic s and kinetic s f or practical applications remain a challenge [Researchers have explored modifications, including morphological changes and nanoparticle additions via high energy ball milling (HEBM). While t hese alterations show improvements in hydrogen storage properties, they often negatively impact gravimetric capacity, theoretically set at 7.6 wt.% for pure Mg [ 6]. Achieving t his full capacity is rar e due to limitations in reaction mechanisms such as the sluggish diffusion of hydrogen through the newly formed MgH 2 on the surface of Mg leading to capacitie s below 4 w t [ Hence a systematic approach that includes both morphological modifications through HEBM and the addition of Ni nanoparticles to pure Mg could help to imp rove the gravimetric capacity of commercially pure M g and kinetics of absorption In this research, we propose a novel two step method of surfactant assisted HEBM to synthesize Mg thin flakes with a thickness of 260 ± 67 nm. This method enables a storage capacity of 4.8 wt.% hydrogen at 350°C and 2 0 bar owing to th e combination of interfacial effects and the shortening of diffusion pathways in one dimension for hydrogen atoms [ 8]. This showcases the potential use of this flake like shaped Mg for efficient hydrogen storage. Additionally, the dispersion of Ni nanoparticles (5 wt.%) on the surface of Mg ultra thin flakes leads to a reduction in the time for maximum absorption from 5 min to 3 min, at the expense of a slight decrease in the hydrogen uptake capacity to approximate ly 4. 5 wt.% at 350°C and 20 bar A Sieverts type apparatus of our own design and construction is employed for pre activation and sorption/desorption tests SEM EDS analysis is conducted to characterize the morphology and elemental composition of the samples before and after hydrogen tests . D uring the activation process the formation of the complex Mg 2 NiH 4 phase is observed through XRD analysis, suggesting potential for lo wer hydrogenation temperatures and improved thermodynamics for the system [ 9]. N i nanoparticles could potentially act as both catalysts and thermodynamic destabilizers of the obtained Mg thin flakes.